Cumulative damage characteristics of tunnel initial support concrete under blasting load - Yan Zhao; Zhuang Zhang; Lijie Ge; Lingling Xu; Huadong Zhao; Mingzan Yu (Scientific Reports)
Abstract Relying on the Beijing-Zhangjiakou high-speed railway Cao Mao Shan tunnel project, blasting vibration monitoring and sound wave testing experiments were carried out. The monitoring results show that the blasting vibration velocity corresponding to the initial support satisfies the Sadowski formula. The results of the sonic test show that with the increase of blasting times, the cumulative damage increases gradually, but the blasting damage increment shows a downward trend. In addition, as the blasting distance decreases, the blasting cumulative damage effect is significant. Through data analysis and curve fitting, the cumulative damage range R cr and critical blasting vibration velocity PPV cr corresponding to blasting construction are obtained respectively. The numerical analysis results show that there is a good exponential function relationship between the cumulative damage range R cr and the corresponding critical blasting vibration velocity PPV cr . The purpose of quantitative control of blasting damage can be achieved by setting the corresponding vibration velocity threshold.